Little tree - Long, Loren (New York, NY : Philomel Books, an imprint of Penguin Group (USA), 2015)
Little Tree is very happy in the forest, where he is surrounded by other little trees and his leaves keep him cool in the heat of summer, but when autumn comes and the other trees drop their leaves, Little Tree cannot be pursuaded to let his go, even after they wither and turn brown.
Keywords: Trees -- Fiction; Seasons -- Fiction; Change -- Fiction; Forest animals -- Fiction; JUVENILE FICTION / Social Issues / New Experience; JUVENILE FICTION / Nature & the Natural World / Environment